Management of epilepsy in women. Issue 5 (May 2019) - Stephen, Linda J; Harden, Cynthia; Tomson, Torbjörn; Brodie, Martin J
Summary: Epilepsy is a common neurological condition in women worldwide. Hormonal changes occurring throughout a woman's life can influence and be influenced by seizure mechanisms and antiepileptic drugs, presenting unique management challenges. Effective contraception is particularly important for women with epilepsy of childbearing potential because of antiepileptic drug-related teratogenicity and hormonal interactions; although studies reveal many women do not receive contraceptive and preconceptual counselling. Management challenges in this population include the higher risk of pregnancy complications and peripartum psychiatric problems than in women without epilepsy. Research is needed to clarify the precise role of folic acid supplementation in prevention of congenital malformations in children born to women with epilepsy. To optimise treatment of low bone density in women with epilepsy, studies investigating bone densitometry frequency and calcium and vitamin D supplements are required. Understanding of the mechanisms linking seizures and the menopause will help to develop effective therapeutic strategies, and advances in managing epilepsy could improve quality of life for women with this condition.